2020
DOI: 10.3390/jof6020083
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Activity of a Paraphaeosphaeria sporulosa-Produced Diketopiperazine against Salmonella enterica

Abstract: A diketopiperazine has been purified from a culture filtrate of the endophytic fungus Paraphaeosphaeria sporulosa, isolated from healthy tissues of strawberry plants in a survey of microbes as sources of anti-bacterial metabolites. Its structure has been determined by nuclear magnetic resonance (NMR) and liquid chromatography–mass spectrometry (LC–MS) analyses and was found to be identical to cyclo(L-Pro-L-Phe) purified from species of other fungal genera. This secondary metabolite has been selected following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The diketopiperazine cyclo(L-Pro-L-Phe) (104, Figure 7), was purified from Paraphaeosphaeria sporulosa, associated with Fragaria x ananassa. Compound 104 displayed activity against Salmonella strains, S1 and S2, with IC 50 values of 7.2 and 7.9 µg/mL and MICs of 71.3 and 78.6 µg/mL, respectively [63].…”
Section: Minor Taxa Of the Ascomycetesmentioning
confidence: 99%
“…The diketopiperazine cyclo(L-Pro-L-Phe) (104, Figure 7), was purified from Paraphaeosphaeria sporulosa, associated with Fragaria x ananassa. Compound 104 displayed activity against Salmonella strains, S1 and S2, with IC 50 values of 7.2 and 7.9 µg/mL and MICs of 71.3 and 78.6 µg/mL, respectively [63].…”
Section: Minor Taxa Of the Ascomycetesmentioning
confidence: 99%
“…The identified cyclic dipeptides belong to the class of Proline–Xaa cyclodipeptides (Xaa denotes unspecified amino acids). These molecules have been reported from various fungal genera and have phytotoxic (compounds 1 , 2 , and 3 ) or antifungal (compound 2 and 4 ) activity (see Wang et al, 2017 for review; Carrieri et al, 2020 ). Additionally, compounds 2 and 3 have been identified from the culture filtrate of endophytic Epichloë typhina ( Song et al, 2015 ; Zhou et al, 2015 ) and have been reported to show antifungal activity ( Wang et al, 1999 ; Magnusson et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity of cyclic dipeptides was evaluated against VERO cell line (African Green Monkey kidney cell line), and no cytotoxicity was recorded for concentrations up to 100 µg/mL [202,221]. Among antibacterial agents, DKP alkaloid-actinozine A, cyclo(2-OH-Pro-L-Leu), but also cyclo(2-OH-D-Pro-L-Leu), cyclo(D-Pro-L-Phe), and cyclo(L-Pro-L-Phe) can be mentioned as well [222,223].…”
Section: Antibacterial Activitymentioning
confidence: 99%